Effect of differential feed on the molting success and survival of horseshoe crab trilobite (Tachypleus gigas) - John, Akbar; Y., Kamaruzzaman; K. C., Ahmed Jalal; S., Hassan.; M., Rozihan (Malaysian Society of Applied Biology, 2017)
Mortality during early life stages of horseshoe crabs especially during the molting of third and fourth instar stage is significantly higher. This is perhaps due to the change in feeding behavior from filter feeding (first and second instar) to active feeding (third instar onwards). Hence, we offered differential microalgae feed (Isochrysis, Spirulina and Isochrysis + Spirulina) toinduce molting and improve survival at third instar stages of Malaysian horseshoe crab (Tachypleus gigas). Third instar T.gigas were fed with 3 different concentration of microalgae [Isochrysis (7.5 × 106 cells/L and 0.75 × 106 n cells/L)], [(Spirulina(1 ml/L and 0. ml/L)], [(Isochrysis + Spirulina: (3.75 × 106 cells of Isochrysis + 0.5 ml spirulina/ L and 0.375 × 106 cells of Isochrysis + 0.25 ml spirulina/L)] every 3 days for 30 days interval and morphometric measures were documented. Results revealed that combination of microalgae feed induce molting and survival rate regardless of concentration employed. Significant difference in molting were observed between control and treated groups regardless of feed concentration (p<0.05). There was no mortality of crabs observed in Isochrysis feed tanks while 25% and 20% mortality of crabs (especially appendage lost) were recorded in spirulina and iso+spirulina feed tanks respectively. Molting was observed in all treatment tanks. We suggest that Isochrysis with the concentration of 7.5 × 106 cells/L can be used to induce faster molting in T. gigas instar stage.